Molar Incisor Hipomineralization, a clinical entity never described before in Costa Rican children - Ulate DDS, Joseph; Gudiño Fernández DDS, MPH, Sylvia (Odovtos - International Journal of Dental Sciences, 2015)
Dental enamel is an unique, highly mineralized tissue from ectodermal origin, characterized by the absence of metabolic activity once its formation is completed. This fact determines that when disturbances occur during its development, defects will be present in the permanent tooth at eruption. This article reports the most important findings published in the scientific literature over the last decade about Molar Incisor Hypomineralization, denomination, histology, classification, signs and symptoms, epidemiology, histology and differential diagnosis.